2015
DOI: 10.1080/21565503.2015.1050411
|View full text |Cite
|
Sign up to set email alerts
|

Social media and senior citizen advocacy: an inclusive tool to resist ageism?

Abstract: With population aging, interest groups demand that governments act to prevent a perceived financial crisis. Senior citizens remain frustrated in their efforts to influence the response of policy-makers. In an effort to strengthen their voice, one group of senior citizens, engaged in a participatory action research project, questioned how online social media could be used in their advocacy efforts. This query led to an examination of the literature with the primary objective of determining what is known about t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(21 citation statements)
references
References 51 publications
0
19
0
2
Order By: Relevance
“…In fact, there are some initiatives of older people to get the attention of policymakers. A participatory action research project from 2015, Exercising Senior Citizenship in an Ageist Society [65], had as a primary objective to understand how social media platforms could be used by senior citizens for purposes of social advocacy. The project initiated an online blog (carewatch.tumblr.com) and stimulated older people to engage in conversation about different forms of ageism.…”
Section: Visual Communication Rights For Senior Citizensmentioning
confidence: 99%
“…In fact, there are some initiatives of older people to get the attention of policymakers. A participatory action research project from 2015, Exercising Senior Citizenship in an Ageist Society [65], had as a primary objective to understand how social media platforms could be used by senior citizens for purposes of social advocacy. The project initiated an online blog (carewatch.tumblr.com) and stimulated older people to engage in conversation about different forms of ageism.…”
Section: Visual Communication Rights For Senior Citizensmentioning
confidence: 99%
“…In this spirit, several studies have explored social media as a space for social and political identity formation and contestation (Bagozzi et al ; Code and Zaparyniuk ; Gabbiadini et al ; Trentham et al ; Yoo et al ). For example, Trentham et al () investigated the use of social media by elderly people to resist ageist stereotypes. Their study revealed how social media was used by the elderly to engage in policy debates, thereby challenging stereotypes of the elderly as disinterested in wider public discussion.…”
Section: Poverty (De)stigmatisation and (Social) Mediamentioning
confidence: 99%
“…Some work has raised questions about what constitutes meaningful social change through online activity on these platforms [17,51,62], with Gladwell [31] questioning the overstated enthusiasm of activism online without change occurring offline and whether a true social movement can be mediated by the Internet alone. The body of work examining social movements online, however, has neglected to study the involvement of the ways older adults in particular discuss social issues in online spaces [69]. Understanding this area can help reveal the role of technology in negotiating social issues more broadly while deepening our understanding of their unique views on pressing social issues.…”
Section: Social Movements and Online Interactionmentioning
confidence: 99%